2018
DOI: 10.5539/ijef.v10n2p108
|View full text |Cite
|
Sign up to set email alerts
|

Digital Currency Risk

Abstract: Digital currencies, such as Bitcoin, have emerged as an alternative form of money, untethered to traditional money and largely unregulated. As such, digital currency represents a wild frontier for investors who might otherwise be shopping for gold or foreign currencies, with serious risks. The present work considers digital currency from a traditional asset pricing perspective. Setting aside risks of seller fraud or currency theft, we examine fluctuation and systematic risk in the price of Bitcoin. From this p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Stoffels (2017) andGilbert and Loi (2018) examine cryptocurrency loadings on the CAPM and Fama French 3-factor models.…”
mentioning
confidence: 99%
“…Stoffels (2017) andGilbert and Loi (2018) examine cryptocurrency loadings on the CAPM and Fama French 3-factor models.…”
mentioning
confidence: 99%
“…If a person makes a poor judgment and suffers a loss, they are more likely to consider that circumstance as dangerous, especially if the loss has an effect on their financial condition ( 2014), which concluded that there is a positive effect of risk perception and making an investment decision, provide evidence for this. There are many cases of people who have lost their assets and even committed suicide because of frustration that their crypto assets have experienced a significant price decline (Gilbert & Loi, 2018). Even though it has a high risk, the behavior of millennials who are known to like to have fun, have fun in their youth nowadays, many even allocate their funds to invest in Crypto (Syakir et al, 2018).…”
Section: Perceived Risk Toward Investment Decisionmentioning
confidence: 99%
“…Finally, disruptive innovations according to Christensen et al, (2015) end up replacing the established businesses. This view can't hold in terms of bitcoin since bitcoin has a limited of 21 million (Gilbert & Loi, 2018), which according to Ciaian et al, (2018), will be reached by 2041.…”
Section: Conclusion and Recommendationmentioning
confidence: 99%
“…Recent research suggested that bitcoin was the first digital currency to be decentralized and continues to be the most widely used online currency (Presthus & O'Malley, 2017). Hence, its success Bitcoin as a digital currency has attracted the attention of many academic scholars who have investigated the blockchains and digital currencies, their intrinsic value, relationship with the banking sector as well as their implications for society (Chan et al, 2017;Fiammetta & Piazza, 2017;Gilbert &Loi, 2018 andWhite et al, 2020), Customer awareness and adoption of the digital currencies (Presthus & O'Malley, 2017;Eigbe, 2018). This study aims to understand the existing literature on digital currencies and in particular the bitcoins.…”
Section: Introductionmentioning
confidence: 99%